Actinomyces denticolens colonisation identified in equine tonsillar crypts - Murakami, S. (BMJ Publishing Group, 2016)
Recently, submandibular abscesses associated with Actinomyces denticolens have been reported in horses. The actinomycotic clumps have been observed in the tonsillar crypts. The aim of this study was to demonstrate colonisation of A denticolens in equine tonsils. Twelve equine tonsils obtained from a slaughterhouse were divided into two parts for histopathological examination and for isolation of A denticolens. When actinomycotic clumps were found in these tonsillar crypts, immunohistochemistry using hyperimmune serum against A denticolens (DMS 20671) was performed on the serial sections. To determine whether Actinomyces-like bacteria isolated using immunoantigenic separation technique were A denticolens, the isolates were analysed for the 16S rRNA gene sequence. Actinomycotic clumps were found in the tonsillar crypts of 11 (91.7 per cent) horses. The clumps were of the saprophytic type accompanied with the feedstuffs, but a few clumps were surrounded by inflammatory cells. A denticolens antigens were immunodetected not only in the clumps of 11 (100 per cent) tonsils, but also in the tonsillar parenchyma. Six isolates obtained from four tonsils showed 99.7–99.9 per cent similarity to A denticolens in the 16S rRNA gene sequence. In horses, the colonisation sites of A denticolens are the tonsils, thus the authors suggest that the tonsils provide the intrinsic infection site for A denticolens.